NEO-COLONIAL DEPENDENCE AND DUALISTIC DEVELOPMENT MODELS: AN EXPLORATION OF THE DEVELOPMENT COMMUNICATION TRAJECTORY IN NIGERIA - Omoera, Osakue Stevenson; Obekpa, Enuwa Evelyn (The Journal of Society and Media, 2019)
Communication has been identified as the underlying factor for human development whether at the socio-scientific, socio-economic or socio-political levels. Globally, development communication has increasingly become a critical component in the pursuit of scientific, economic, agricultural, social and political advancement of human societies. It is within this context that this study uses the historical-analytic, sociological and direct observation methods to appraise the neo-colonial and dualistic development models. In doing this, it highlights critical inferences on how development communication could be more beneficial to developing countries in Africa, specifically Nigeria, by way of communicating science and producing higher end products in the vital sectors of the economy. The conclusion reached is that through the dynamics of development communication the Nigerian populace can be mobilised and empowered to be productively creative in their contributions to Nigeria?s gross domestic product (GDP) and improve their living standard.